Evaluation of Azolla Compost as Bio-fertilizer in Carp Culture - Ansal, M.D.; Kaur, K.; Kaur, V.I. (Indian Journal of Animal Nutrition, 2018)
Efficacy of Azolla compost (AC), as bio-fertilizer in carp culture, was evaluated through a 150 days grow out trial in cemented tanks stocked with common carp fry (BW-0.60-0.61g) @ 50,000/ha. The study comprised of four treatments and three replicates per treatment, where cow dung (CD), AC and CD +AC combinations (CD+AC, 1: 1 and CD+AC, 1: 3) were used to manure the tanks. The tank manured with CD served as control. In all the treatments, the manure was added at the rate of 20,000 kg/ha/yr, where Â¼th of the dose was added 15days prior to stocking of fish, while rest of the manure was added in equal doses every week. Better water quality in terms of dissolved oxygen (DO) and ammonia content was observed in AC treatments. Significantly higher DO content (P